Knowledge Management In Higher Learning Institutions: A Case Study Of Universiti Putra Malaysia (UPM) - Mohd Mahdee, Junainah (2007)
The main focus of this study has been stressed to SWOT analysis in which consists of the internal and external analysis of UPM as a whole. From the analyses obtained, further examination can be carried out on how the Knowledge Management practices are applied in helping the productivity or performance of UPM. There is also evaluation and control in new developments as well as corrective adjustments.